Wilson and Gisvold's textbook of organic medicinal and pharmaceutical chemistry - Wilson, Charles Owens, 1911-; Beale, John Marlowe; Block, John H. (Baltimore, MD : Lippincott Williams & Wilkins, 2011)
"For over half a century, Wilson and Gisvold's Textbook of Organic Medicinal and Pharmaceutical Chemistry has served the discipline of medicinal chemistry for both graduate and undergraduate pharmacy and chemistry students as well as practicing pharmacists. Fully updated for the Twelfth Edition, the book begins with the fundamental principles of chemistry, biochemistry, and biology that underlie the discipline of medicinal chemistry. These principles are then applied to understanding the properties, mode of action, therapeutic applications, and limitations of various pharmaceutical agents. The subject matter is organized by pharmaceutical and therapeutic classes, providing a bridge between the basic sciences and clinical practice. The text contains many tables for quick reference to names, formulations, dosages, and applications. This edition includes chapter review questions and cases." "A companion website provides online updates of medicinal chemistry structures and an image bank for faculty."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Pharmaceutical chemistry; Chemistry, Organic; Chemistry, Pharmaceutical; Chemistry, Organic